2021
DOI: 10.3390/vaccines9080932
|View full text |Cite
|
Sign up to set email alerts
|

TBE Vaccination Breakthrough Cases—Does Age Matter?

Abstract: Tick-borne encephalitis (TBE) vaccines are highly effective in preventing TBE and vaccine failures (VF) are rare events. In this study, we compared the age distribution of TBE cases and TBE VF in three endemic countries: Sweden, Southern Germany, and Latvia. While the age distribution of TBE cases was similar for those <50 years versus those ≥50 years in all three countries, in Sweden, a higher proportion of VF cases was ≥50 years, whereas most VF cases in Latvia were <50 years of age and more evenly dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…An additional limitation is that, while we found TBE VE appeared similar between age groups, as we matched cases and controls by age we were unable to directly compare VE values. While some studies have demonstrated reduced serological responses to TBE vaccination and increased vaccine breakthrough in older individuals,17 20 30 31 other work has shown vaccination breakthrough to be comparable between older and younger age groups, and that VE remains high even among those aged 60+ 32 33. Clarifying how TBE VE is impacted by age remains an important area warranting further study.…”
Section: Discussionmentioning
confidence: 99%
“…An additional limitation is that, while we found TBE VE appeared similar between age groups, as we matched cases and controls by age we were unable to directly compare VE values. While some studies have demonstrated reduced serological responses to TBE vaccination and increased vaccine breakthrough in older individuals,17 20 30 31 other work has shown vaccination breakthrough to be comparable between older and younger age groups, and that VE remains high even among those aged 60+ 32 33. Clarifying how TBE VE is impacted by age remains an important area warranting further study.…”
Section: Discussionmentioning
confidence: 99%
“…An association between age and vaccine breakthroughs was observed in a Swedish study. However, it is noteworthy that approximately half of the patients in whom vaccine failure was observed had comorbidities affecting the immune system, suggesting that other factors could explain the higher proportion of vaccine failure in subjects aged ≥50 years [61]. However, there is no evidence that an additional priming dose is of "immunological" or clinical benefit [61,62].…”
Section: Focus On Fsme-immun/ticovac Vaccinementioning
confidence: 99%
“…High field vaccine effectiveness, >90%, has been demonstrated in several settings and across all ages, including people ≥60 years old [ 24 , 25 ]. However, breakthrough TBE, despite vaccination, has been noted across Europe [ 26 , 27 ]. Some authors quote that these vaccine failures appear to occur more often in patients >50 years of age, possibly due to age-related weakening of the immune system, though the exact cause has not been elucidated [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, breakthrough TBE, despite vaccination, has been noted across Europe [ 26 , 27 ]. Some authors quote that these vaccine failures appear to occur more often in patients >50 years of age, possibly due to age-related weakening of the immune system, though the exact cause has not been elucidated [ 27 , 28 , 29 ]. However, this is not generally accepted and recent studies do not confirm a higher vaccine failure rate in the elderly [ 23 ].…”
Section: Introductionmentioning
confidence: 99%